1,8-Bis(dimethylamino)naphthyl-2-ketimines: Inside vs outside protonation - Antonov, A. S.; Pozharskii, A. F.; Tolstoy, P. M.; Filarowski, A.; Khoroshilova, O. V. (Beilstein Journal of Organic Chemistry, 2018)
The structure and protonation behaviour of four ortho-arylketimines of 1,8-bis(dimethylamonio)naphthalene with a different number of methoxy groups in an aromatic substituent were investigated in solution by NMR (acetone, DMSO, MeCN), in solid state by X-ray analysis and in the gas phase by DFT calculations. Both mono- and diprotonated species were considered. It has been shown that E-isomers of neutral imines can be stabilised by an intramolecular C=N−H···OMe hydrogen bond with a neighbouring methoxy group. Electron-donating OMe groups dramatically increase the basicity of the imino nitrogen, forcing the latter to abstract a proton from the proton sponge moiety in monoprotonated forms. The participation of the out-inverted and protonated 1-NMe2 group in the Me2N−H···NH=C hydrogen bond is experimentally demonstrated. It was shown that the number and position of OMe groups in the aromatic substituents strongly affects the rate of the internal hindered rotation of the NH2+ fragment in dications.
Keywords: hydrogen bond; imine; NMR; proton sponge; superbase